Integrating AI in Education Management: Strategies, Challenges, and Opportunities at SMA Kramat Dukupuntang - Muhammad Yasir Arafah (Civiliza Publishing, Indonesia., 2026)
The development of Artificial Intelligence (AI) has had a significant impact on various sectors, including education. The integration of AI in education management is one of the important strategies to improve the effectiveness of school management, the quality of academic services, and data-driven decision-making. This research aims to analyze the AI implementation strategy, the challenges faced, and the opportunities that arise in the management of education at Kramat Dukupangkang High School. The research uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation studies. The results of the study show that the application of AI can support school administration, student data management, learning monitoring, and evaluation of educational performance more effectively and efficiently. The strategies implemented include strengthening teachers' digital literacy, providing technological infrastructure, and developing school policies based on digital transformation. However, AI implementation still faces various challenges such as limited human resources, uneven technological infrastructure, data security issues, and resistance to change. On the other hand, AI opens up great opportunities for improving the quality of education through personalized learning, faster information management, and more accurate decision-making. This study concludes that the successful integration of AI in education management requires school policy support, improvement of digital competence of educators, and collaboration between all education stakeholders.